2022
DOI: 10.15252/emmm.202115343
|View full text |Cite
|
Sign up to set email alerts
|

Lactate dehydrogenases promote glioblastoma growth and invasion via a metabolic symbiosis

Abstract: Lactate is a central metabolite in brain physiology but also contributes to tumor development. Glioblastoma (GB) is the most common and malignant primary brain tumor in adults, recognized by angiogenic and invasive growth, in addition to its altered metabolism. We show herein that lactate fuels GB anaplerosis by replenishing the tricarboxylic acid (TCA) cycle in absence of glucose. Lactate dehydrogenases (LDHA and LDHB), which we found spatially expressed in GB tissues, catalyze the interconversion of pyruvate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 69 publications
1
31
0
Order By: Relevance
“…Upon being recognized by the promoter region of the Ldha gene locus, transcription factors (TFs) (Sukonina et al, 2019), such as hypoxia‐inducible factor‐1 (HIF‐1) (Koukourakis et al, 2003; Semenza et al, 1996), stimulate the expression of Ldha , subsequently leading to the reprogramming of glucose metabolism. Inhibiting LDHA expression may reduce the invasive and metastatic potential of cancer cells by decreasing their proliferation ability and reversing their resistance to chemotherapy (Guyon et al, 2022); however, whether manipulating LDHA can produce beneficial impact on cardiac fibrosis is still unclear. Also, whether and how LDHA is modulated in cardiac fibroblasts in response to fibrotic stimuli remains poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Upon being recognized by the promoter region of the Ldha gene locus, transcription factors (TFs) (Sukonina et al, 2019), such as hypoxia‐inducible factor‐1 (HIF‐1) (Koukourakis et al, 2003; Semenza et al, 1996), stimulate the expression of Ldha , subsequently leading to the reprogramming of glucose metabolism. Inhibiting LDHA expression may reduce the invasive and metastatic potential of cancer cells by decreasing their proliferation ability and reversing their resistance to chemotherapy (Guyon et al, 2022); however, whether manipulating LDHA can produce beneficial impact on cardiac fibrosis is still unclear. Also, whether and how LDHA is modulated in cardiac fibroblasts in response to fibrotic stimuli remains poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies indicate that malignant brain tumors might also be particularly dependent on mitochondrial mechanisms. A recent elegant example of this was a study by Gyon and collaborators where they demonstrated an important role for mitochondrial adaptation in response to radiation therapy in glioblastoma (GB) [ 13 ]. Production of lactate, an end‐product of mitochondrial glycolysis and an important survival factor for GB cells, is catalyzed by lactate dehydrogenase A and B (LDHA and LDHB) proteins.…”
mentioning
confidence: 99%
“…Production of lactate, an end‐product of mitochondrial glycolysis and an important survival factor for GB cells, is catalyzed by lactate dehydrogenase A and B (LDHA and LDHB) proteins. The authors demonstrated that in glioblastoma tissue, LDHA and LDHB are spatially differentially expressed and only a few cells expressed both isoforms [ 13 ]. Functionally, lactate production was only inhibited by co‐targeting of both LDHA and B isoforms indicating that in the absence of one isoform, the other isoform can compensate for its activity.…”
mentioning
confidence: 99%
See 2 more Smart Citations